Perbedaan Resiliensi Anak Dari Keluarga Broken Home Dengan Anak Keluarga Utuh - winanti, hepy rizki septia (Counseling AS SYAMIL: Jurnal Ilmiah Bimbingan Konseling Islam, 2022)
The family is a social group that is eternal, confirmed in a marriage that influences heredity and the environment as an important dimension for the individual, and the family is an important place where individuals, especially children, gain a basis in shaping their abilities to become successful people in society. The family consists of individuals namely father, mother and children as the nuclear family. This study aims to describe the differences in the resilience of children from broken home families with children from intact families. This study used descriptive qualitative method. Case study data collection by interview (curriculum vitae), observation, document review, survey (results) and any data to describe a case in detail. The results of this study are on aspects of emotion regulation, impulse control, empathy, problem analysis skills and increasing positive aspects as well as sources of resilience